"They should stay at their desk until the work's done": a qualitative study examining perceptions of sedentary behaviour in a desk-based occupational setting. (December 2015) - Cole, Judith; Tully, Mark; Cupples, Margaret
Abstract Background Workplace sedentary behaviour is a priority target for health promotion. However, little is known about how to effect change. We aimed to explore desk-based office workers' perceptions of factors that influenced sedentary behaviour at work and to explore the feasibility of using a novel mobile phone application to track their behaviours. Methods We invited office employees (n = 12) and managers (n = 2) in a software engineering company to participate in semi-structured interviews to explore perceived barriers and facilitators affecting workplace sedentary behaviour. We assessed participants' sedentary behaviours using an accelerometer before and after they used a mobile phone application to record their activities at self-selected time intervals daily for 2 weeks. Interviews were analysed using a thematic framework. Results Software engineers (5 employees; 2 managers) were interviewed; 13 tested the mobile phone application; 8 returned feedback. Major barriers to reducing workplace sedentary behaviour included the pressure of 'getting the job done', the nature of their work requiring sitting at a computer, personal preferences for the use of time at and after work, and a lack of facilities, such as a canteen, to encourage moving from their desks. Facilitators for reduced sedentariness included having a definite reason to leave their desks, social interaction and relief of physical and mental symptoms of prolonged sitting. The findings were similar for participants with different levels of overall physical activity. Valid accelerometer data were tracked for four participants: all reduced their sedentary behaviour. Participants stated that recording data using the phone application added to their day's work but the extent to which individuals perceived this as a burden varied and was counter-balanced by its perceived value in increasing awareness of sedentary behaviour. Individuals expressed a wish for flexibility in its configuration. Conclusions These findings indicate that employers' and employees' perceptions of the cultural context and physical environment of their work, as well as personal factors, must be considered in attempting to effect changes that reduce workplace sedentary behaviour. Further research should investigate appropriate individually tailored approaches to this challenge, using a framework of behaviour change theory which takes account of specific work practices, preferences and settings.